2021
DOI: 10.1094/pdis-12-20-2730-re
|View full text |Cite
|
Sign up to set email alerts
|

Universal Primers for Rapid Detection of Six Pospiviroids in Solanaceae Plants Using One-Step Reverse-Transcription PCR and Reverse-Transcription Loop-Mediated Isothermal Amplification

Abstract: A number of viruses and viroids infect solanaceous plants causing severe yield losses. Several seed-borne viroids are currently listed as quarantine pathogens in many countries. Among them, columnea latent viroid (CLVd), pepper chat fruit viroid (PCFVd), potato spindle tuber viroid (PSTVd), tomato apical stunt viroid (TASVd), tomato chlorotic dwarf viroid (TCDVd), and tomato planta macho viroid (TPMVd) are of major concerns. The objective of this study was to design and test universal primers that could be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The assay was repeated using the same dilution series in a RotorGene Q The copy numbers of the trRNA dilution series amplification curves are coloured as follows; 6.1 × 10 12 -red, 6.1 × 10 11 -green, 6.1 × 10 10 yellow, 6.1 × 10 9 -blue, 6.1 × 10 8 -pink, 6.1 × 10 7 -black, 6.1 × 10 6orange, 6.1 × 10 5 -purple RT-LAMP assays have been designed previously to detect sequence variants using degenerate bases and mismatches to particular variants in primers with success (James et al 2010;Park et al 2013;Komatsu et al 2015;Tangkanchanapas et al 2018). A similar approach was employed in this study to cover as many CEVd variants as possible, and the results support other studies where RT-LAMP was shown to be a successful diagnostic tool for viroid detection in plants (Tangkanchanapas et al 2018;Verma et al 2020;Tseng et al 2021).…”
Section: Detection Comparison Between Rt-lamp With Rt-qpcr Assayssupporting
confidence: 80%
See 1 more Smart Citation
“…The assay was repeated using the same dilution series in a RotorGene Q The copy numbers of the trRNA dilution series amplification curves are coloured as follows; 6.1 × 10 12 -red, 6.1 × 10 11 -green, 6.1 × 10 10 yellow, 6.1 × 10 9 -blue, 6.1 × 10 8 -pink, 6.1 × 10 7 -black, 6.1 × 10 6orange, 6.1 × 10 5 -purple RT-LAMP assays have been designed previously to detect sequence variants using degenerate bases and mismatches to particular variants in primers with success (James et al 2010;Park et al 2013;Komatsu et al 2015;Tangkanchanapas et al 2018). A similar approach was employed in this study to cover as many CEVd variants as possible, and the results support other studies where RT-LAMP was shown to be a successful diagnostic tool for viroid detection in plants (Tangkanchanapas et al 2018;Verma et al 2020;Tseng et al 2021).…”
Section: Detection Comparison Between Rt-lamp With Rt-qpcr Assayssupporting
confidence: 80%
“…RT-LAMP assays have been developed for citrus tristeza virus (CTV) (Warghane et al 2017;Selvaraj et al 2019), citrus leaf blotch virus (Liu et al 2019) and Indian citrus ringspot virus (Kokane et al 2021) but not so far for any citrus-infecting viroids. A RT-LAMP assay has also been developed to allow the simultaneous detection of six pospiviroids, but CEVd is not among the target pathogens (Tseng et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RNA dilutions up to 40-fold were found to reduce the inhibitory compounds in the RNA extracts. The combination of single-step RT-LAMP and calorimetric detection has been widely used for virus detection in plants and for COVID-19 diagnosis [ 30 , 31 , 45 , 46 , 47 ]. To date, we have analyzed over 150,000 samples using MFDetect TM to detect several other pathogens, including viruses and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…RT-LAMP uses four to six primers to target and amplify a specific region of the pathogen, and the reaction occurs isothermally in a single tube. RT-LAMP can be designed for detecting multiple viroids using a generic primer or universal set of primers [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the virus's target of the coat protein gene, they utilized four different primers ( Kokane et al., 2021 ). The detection was based on visualization of change of color after adding SYBR Green I during the process ( Tseng et al., 2021 ), developed a test to identify six different viroids using one-step RT-PCR and RT-LAMP with ubiquitous primers – columnea latent viroid (CLVd), pepper chat fruit viroid (PCFVd), potato spindle tuber viroid (PSTVd), tomato apical stunt viroid (TASVd), tomato chlorotic dwarf viroid (TCDVd), and tomato planta macho viroid (TPMVd). The outcomes showed that six pospiviroids from solanaceae seeds and plants could be amplified using a pair of degenerate primers in a one-step RT-PCR.…”
Section: Modern Biosensor Technology For Plant Pathogen Detectionmentioning
confidence: 99%